HUBUNGAN POLIFARMASI DAN TEMUAN POTENSI INTERAKSI OBAT PADA PERESEPAN PASIEN ANAK DI APOTEK BUKIT SARI SEMARANG TAHUN 2021 - Dariyati, Nita; Suwarni, Sri; Pitarisa, Agustina Putri; Serang, Yithro; Leki, Karol Giovani Battista (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Polypharmacy is still frequent and very common in pediatric prescribing. Polypharmacy can increase the potential for drug interactions. Most of which have a detrimental impact on patient therapy. Drug interactions are considered clinically important when they result in increased toxicity or reduced therapeutic effectiveness. This study aims to determine the relationship between polypharmacy and the potential for drug interactions in the prescription of pediatric patients at Bukit Sari Pharmacy Semarang for the 2021 period. This research is a type of quantitative descriptive analysis research. Research data were obtained retrospectively in the period January - December 2021 which is based on the prescription data of pediatric patients at Bukit Sari Pharmacy Semarang for the 2021 period. The sampling technique used proportional random sampling method where samples were taken from pediatric patient prescriptions that met the inclusion criteria. Of the 270 prescription sheets analyzed, 160 prescription sheets experienced polypharmacy. Percentage of drug interaction events drug interaction was 36.7%. Statistical analysis using the Spearmans Test obtained a p value